Perubahan Sifat Organoleptik Tahu Selama Penyimpanan Pada Suhu Kamar (The changing characteristic of Tofu Organoleptik During Storage at room temperature) (Jurnal Teknologi Pangan, 2015)
P { margin-bottom: 0.08in; } Abstract The development of the industry tofu at this moment is still stuck on the issue of the limited keep out capacity. For eligible regular conditions, consumed on tofu last only about 10 minutes at room temperature, more of the time usually have become sour and then rot and unfit for consumption. To extend the save process is done preserving tofu that soaking in water and soaking in turmeric 7% solution for 90 minutes. Soaking tofus Microbe shows growth in water of 4,48 log CFU/g of storage during 24 hours. Soaking in solution tofu turmeric 7% showed growth of microbes of 3,421 log CFU/g of storage during 24 hours. The purpose of this study was to examine whether there is influence between preserving methods tofu to total total bacteria, Escherichia coli, Salmonella out of storage for a total of 0, 12, 24, 36 and 48 hours at room temperature, and to tofu of any growth of Eschericia coli, Salmonella, as well as the changing nature of the organoleptik tofu during storage at room temperature. The results showed that there is a real difference between the control and the preservation of two methods of total microbes on storage 12-48 hours, a total of Escherichia coli on storage 24-48 hours and a total of Salmonella on storage 24-48 hours. There is no real difference between the control and the preservation of the total microbial method on storage 0 hours, the total storage on Escherichia coli 0-12 hours and a total of Salmonella on storage 0-12 hours. Tofu the controls have the Save 12 hours with a total of 3,437 bacteria log CFU/gr, E coli 2,021 log CFU/g of Salmonella, 0 log CFU/g of average, the smell of 1,267 (no foul – rather foul), 1,133 appearance average (not slimy-somewhat slimy), average 3,733 texture (a little loud-soft). Know that water soaked can still be consumed up to 24 hours and has a total of 3,414 bacteria log CFU/gr, E coli 2,276 log CFU/g of Salmonella, 0 log CFU/g, average smell 2 (bit rot) 1.2 appearance average (not slimy-somewhat slimy), average 4 texture (soft). Know the soaking solution of 7% for 90 turmeric can be consumed up to 36 hours and has a total of 3,491 bacteria log CFU/gr, E coli 2,203 log CFU/g of Salmonella, 0 log CFU/g of average, the smell of 1,267 (no foul – rather foul), an average of 2.2 to be portrayed (somewhat slimy-slimy), an average of 2,600 texture (rather loud)   Keyword : Escherichia coli, Salmonella, tofu   Abstrak Pengembangan industri tahu pada saat ini masih terbentur pada masalah terbatasnya daya simpan tahu. Untuk layak dikonsumsi pada kondisi biasa, tahu hanya bertahan sekitar 10 jam pada suhu kamar, lebih dari waktu tersebut biasanya sudah menjadi asam kemudian membusuk dan tidak layak dikonsumsi. Untuk memperpanjang masa simpan tahu dilakukan proses pengawetan yaitu perendaman dalam air dan perendaman dalam larutan kunyit 7% selama 90 menit. Perendaman tahu dalam air menunjukkan pertumbuhan mikroba sebesar 4,48 log CFU/gr selama penyimpanan 24 jam. Perendaman tahu dalam larutan kunyit 7% menunjukkan pertumbuhan mikroba sebesar 3,421 log CFU/gr selama penyimpanan 24 jam. Tujuan penelitian ini adalah mengkaji ada tidaknya pengaruh antara metode pengawetan tahu terhadap total bakteri, total Escherichia coli, total Salmonella tahu selama penyimpanan 0, 12, 24, 36 dan 48 jam pada suhu kamar, dan untuk mengetahui adanya pertumbuhan Eschericia coli, Salmonella, serta perubahan sifat organoleptik tahu selama penyimpanan pada suhu kamar. Hasil penelitian menunjukkan bahwa terdapat beda nyata antara kontrol dan dua metode pengawetan terhadap total mikroba pada penyimpanan 12-48 jam, total Escherichia coli pada penyimpanan 24-48 jam dan total Salmonella pada penyimpanan 24-48 jam. Tidak terdapat beda nyata antara kontrol dan metode pengawetan terhadap total mikroba pada penyimpanan 0 jam, total Escherichia coli pada penyimpanan 0-12 jam dan total Salmonella pada penyimpanan 0-12 jam. Tahu pada kontrol mempunyai masa simpan 12 jam dengan total bakteri 3,437 log CFU/gr, E coli 2,021 log CFU/gr, Salmonella 0 log CFU/gr, rata-rata bau 1,267 (tidak busuk-agak busuk), rata-rata kenampakan 1,133 (tidak berlendir-agak berlendir), rata-rata tekstur 3,733 (agak keras-lunak). Tahu yang direndam air masih dapat dikonsumsi sampai 24 jam dan memiliki total bakteri 3,414 log CFU/gr, E coli 2,276 log CFU/gr , Salmonella 0 log CFU/gr, rata-rata bau 2 (agak busuk), rata-rata kenampakan 1,2 (tidak berlendir-agak berlendir), rata-rata tekstur 4 (lunak). Tahu dengan perendaman larutan kunyit 7% selama 90 dapat dikonsumsi sampai 36 jam dan memiliki total bakteri 3,491 log CFU/gr, E coli 2,203 log CFU/gr, Salmonella 0 log CFU/gr, rata-rata bau 1,267 (tidak busuk-agak busuk), rata-rata kenampakan 2,2 (agak berlendir-berlendir), rata-rata tekstur 2,600 (agak keras-keras)   Kata kunci : Escherichia coli, Salmonella, tahu